Assessing opportunities and constraints for biofuel development in sub-Saharan Africa - Maltitz, G. von; Staffor, W. (Center for International Forestry Research, 2011)
Sustainable biofuel production should provide opportunities for sub-Saharan African countries and their inhabitants, especially in impoverished rural areas. Biofuel feedstock production has the potential to bring job opportunities and earnings, but this should not be at the cost of existing livelihoods and the local environment. Biofuels also have the potential to increase energy security in these countries for both transportation and household needs. Sub-Saharan African biofuel feedstock production projects can be classified into 4 distinct models based on production scales (small- versus large-scale farm/plantations) and on the intended use of the biofuel (local versus national). The first type embraces large corporate plantations to supply the market for liquid transport fuel blends. The second type comprises small-scale producers linked to the corporate producers. The third type involves small-scale producers supplying the local energy needs of farmers and villages. The fourth and rarest type is linked to the large corporate plantations, to meet the corporation’s own energy needs. The introduction of foreign-owned, large-scale corporate plantations producing biofuel for transport fuel blends causes the most concern in sub-Saharan Africa, as their scale and ownership arrangements may disrupt rural livelihoods and affect access rights to land resources. However, these projects can also bring job opportunities, thereby providing alternative sources of income for poor communities. This working paper assesses mechanisms for limiting the negative impacts while maximising national benefit capture. Market-based mechanisms versus legal and policy mechanisms to enhance long-term sustainability are also discussed.